Penataan Kabel dan Pipa Bawah Laut di Perairan Indonesia Menurut Hukum Internasional - Suripatty, Jesica Martha; Baadilla, Efie; Waas, Richard Marsilio (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: This research discusses the problem of submarine cable and pipeline arrangement in Indonesian waters according to international law, in this case UNCLOS 1982 contains provisions to regulate various marine zones with different legal status.Purposes of the Research: To show the provisions of international law regarding the arrangement of submarine cables and pipes in Indonesian waters.Methods of the Research: This study uses the juridical normative method which is carried out by examining legal materials related to the problem being studied.Results of the Research: The results show that the arrangement of submarine cables and pipes in Indonesian waters is contained in UNCLOS 1982 which includes Inland Waters, Territorial Seas, Additional Zones, Exclusive Economic Zones, Continental Shelf, High Seas and International Seabed Areas. Meanwhile, a more specific regulation is regulated in national law, which is cross-sectoral in nature, resulting in submarine cable and pipeline arrangement which is not optimal.